Perfect Conductor Bodies of Revolution in Hertzian Electrodynamics - Polat, Burak; Dasbasi, Ramazan (IEEE, 2021)
Electromagnetic fields generated or scattered by perfectly conducting bodies of revolution in rotational motion are investigated in the stationary reference frame in the context of Hertzian Electrodynamics. The Hertz-Heaviside field equations that describe the physical mechanism and the corresponding radiation integrals are derived with emphasis on the contribution by convection currents. Explicit expressions of the fields due to static sources are obtained and scattering mechanisms that are insensitive to rotation are described. Results of an experimental test of plane wave scattering by a rotating sphere in a semi-anechoic chamber are provided.
Keywords: bodies of revolution; electromagnetic radiation; electromagnetic scattering; Hertzian Electrodynamics; moving media; SCATTERING; ELECTROMAGNETISM; FIELDS; Engineering